17-AAG and Apoptosis, Autophagy, and Mitophagy in Canine Osteosarcoma Cell Lines. (May 2017) - Massimini, M.; Palmieri, C.; De Maria, R.; Romanucci, M.; Malatesta, D.; De Martinis, M.; Maniscalco, L.; Ciccarelli, A.; Ginaldi, L.; Buracco, P.; Bongiovanni, L.; Salda, L. Della
Canine osteosarcoma is highly resistant to current chemotherapy; thus, clarifying the mechanisms of tumor cell resistance to treatments is an urgent need. We tested the geldanamycin derivative 17-AAG (17-allylamino-17-demethoxygeldanamycin) prototype of Hsp90 (heat shock protein 90) inhibitors in 2 canine osteosarcoma cell lines, D22 and D17, derived from primary and metastatic tumors, respectively. With the aim to understand the interplay between cell death, autophagy, and mitophagy, in light of the dual effect of autophagy in regulating cancer cell viability and death, D22 and D17 cells were treated with different concentrations of 17-AAG (0.5 μM, 1 μM) for 24 and 48 hours. 17-AAG-induced apoptosis, necrosis, autophagy, and mitophagy were assessed by transmission electron microscopy, flow cytometry, and immunofluorescence. A simultaneous increase in apoptosis, autophagy, and mitophagy was observed only in the D22 cell line, while D17 cells showed low levels of apoptotic cell death. These results reveal differential cell response to drug-induced stress depending on tumor cell type. Therefore, pharmacological treatments based on proapoptotic chemotherapy in association with autophagy regulators would benefit from a predictive in vitro screening of the target cell type.